A descriptive grammar of early Old Japanese prose - Bentley, John R. (Brill's Japanese studies library ;, 2001)
The oldest written stage of the Japanese language forms the subject of John Bentley's important volume. The underlying texts (also presented here) are those of the religious liturgies (norito) and imperial edicts (A.D. 685).